2008
DOI: 10.1111/j.1442-9993.2007.01826.x
|View full text |Cite
|
Sign up to set email alerts
|

Spatial distribution of communal nests in a colonial breeding bird: benefits without costs?

Abstract: The spatial organization of individuals, or groups of individuals, within a population can provide valuable information about social organization and population dynamics. We analysed the spatial distribution of nests of the sociable weaver (Philetairus socius) on two farms in the Kalahari. Sociable weavers build large communal nests on big savannah trees, forming a pattern of trees with and without nests. We used two spatial statistics, Ripley's K and the pair correlation function, to describe characteristics … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
7
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 32 publications
2
7
0
Order By: Relevance
“…A variation from clumped to random or regular distribution with increasing spatial scale was reported for other nesting animals (e.g. Gießelmann et al 2008) and confirmed once more how multiple-scale analyses are necessary to finely describe spatial organization. The importance of female-female attraction during nest establishment is in accordance with that observed previously for another digger wasp, Stizus continuus (Polidori et al 2008).…”
Section: Discussionsupporting
confidence: 78%
See 1 more Smart Citation
“…A variation from clumped to random or regular distribution with increasing spatial scale was reported for other nesting animals (e.g. Gießelmann et al 2008) and confirmed once more how multiple-scale analyses are necessary to finely describe spatial organization. The importance of female-female attraction during nest establishment is in accordance with that observed previously for another digger wasp, Stizus continuus (Polidori et al 2008).…”
Section: Discussionsupporting
confidence: 78%
“…Gießelmann et al. ) and confirmed once more how multiple‐scale analyses are necessary to finely describe spatial organization. The importance of female–female attraction during nest establishment is in accordance with that observed previously for another digger wasp, Stizus continuus (Polidori et al.…”
Section: Discussionmentioning
confidence: 73%
“…Similar to what has been found in marine colony breeders, the main factors determining where a nest would be located in an existing colony, seems to be highly correlated with physically-available space within an previously-selected tree [14], [17], [18], [48]. The agreement in explanatory variables between marine bird colonies and weaverbird colonies points to common limitations and trade-offs that determine the location of individuals within the colonies.…”
Section: Discussionsupporting
confidence: 68%
“…As an evolutionary response to challenges of group living across different environments, group members display certain patterns of organization or behavior [1] [4] . Individuals might adjust their location depending on environmental factors such as air temperature and wind [5] – [13] , or social elements like territoriality and proximity to other species [1] , [2] , [14] [18] . Distributions may also depend to some degree on the physical limitations of the group or when being studied, the scale of the study [3] , [4] , [19] .…”
Section: Introductionmentioning
confidence: 99%
“…Among the statistical developments, the use of point process models (PPMs) as species distribution models has received much attention (reviewed in . These models comprised of the locations of fixed objects in space such as the trees in a forest (Lin et al 2011) or the nests of birds (Gießelmann et al 2008) or ants (Li et al 2016); but also can be snapshots of the locations of moving organisms such as whales (Waagepetersen and Schweder 2006) and wild ungulates (Hibert et al 2010). While the objects themselves may be idealized as infinitesimal points in PPMs (for an exception, see Wiegand et al 2006), in reality this is often false (e.g., a tree has a crown).…”
Section: Rdamentioning
confidence: 99%